2010
DOI: 10.1111/j.1742-6723.2010.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for central venous catheter placement in Australasian emergency departments: Potential barriers to more widespread use

Abstract: We found that only 37% of FACEM respondents routinely used US to guide placement of CVCs and a number of barriers to more frequent use are identified. Practices and opinions regarding US use differed significantly between routine and non-routine users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In another study, Matera and colleagues found that 37% of Australasian emergency physicians use US to guide placement of central venous access catheters. Reasons for not using US guidance included concerns that it might take too long, and not having done an US course …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Matera and colleagues found that 37% of Australasian emergency physicians use US to guide placement of central venous access catheters. Reasons for not using US guidance included concerns that it might take too long, and not having done an US course …”
Section: Introductionmentioning
confidence: 99%
“…Reasons for not using US guidance included concerns that it might take too long, and not having done an US course. 12 Little information is known about the use of EDUS by individual ACEM Trainees and emergency physicians.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] The published evidence to date suggests that ultrasound guidance remains underused by emergency physicians. [21][22][23][24] To our knowledge, no prior studies have investigated the recent trends in the use of ultrasound guidance for central venous catheterization. The objectives of this study were to assess the selfreported frequency of use of ultrasound guidance for central venous catheterization by emergency medicine (EM) residents, describe residents' perceptions regarding the use of ultrasound guidance, and identify barriers to the use of ultrasound guidance.…”
mentioning
confidence: 99%
“…The ultrasound-guided CVC is beneficial in improving success rate and reducing the incidence of complications such as arterial puncture, pneumothorax, and catheter-associated blood stream infection [16], [17]. Therefore, the use of real-time ultrasound-guided CVC has been commonly recommend in clinical practice [4], [5], [7], [8], [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasound-guided CVC is recommended as a standard technique, several reasons such as the limited availability of ultrasound machine, lack of training, or longer procedure time can hinder the widespread use of ultrasound device in CVC [6], [9][11]. Particularly in emergency situation, which requires urgent CVC without ultrasound device, the landmark-guided technique can be useful and required to be practiced.…”
Section: Introductionmentioning
confidence: 99%